3X/3X+2Y=3/5Y+12X=-1(要步骤)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 23:03:33
3X/3X+2Y=3/5Y+12X=-1(要步骤)3X/3X+2Y=3/5Y+12X=-1(要步骤)3X/3X+2Y=3/5Y+12X=-1(要步骤)3X/3X+2Y=-13x=-3x-2y6x=-2
3X/3X+2Y=3/5Y+12X=-1(要步骤)
3X/3X+2Y=3/5Y+12X=-1(要步骤)
3X/3X+2Y=3/5Y+12X=-1(要步骤)
3X/3X+2Y=-1
3x=-3x-2y
6x=-2y
y=-3x
3/(5y+12x)=-1
5y+12x=-3
-15x+12x=-3
-3x=-3
x=1
y=-3
1、①3x/3x+2y=-1 ②3/5y+12x=-1
2、①求得y=-3代入②
3、②3/5*-3+12x=-1
12x=-1+3/15
x=-0.8-12
x=-12.8
4、x= -12.8 y= -1
(x-y)/(x+y)=3求( 3x-2y-1)/(x+y-5)
已知x-y/x+y=3,求代数式5(x-y)/x+y-x+y/2(x-y)
{(x+y)/2+(x-y)/3=1,(x+y)-5(x-y)=2.求x=?,y=?
化简[(3x+4y)^2-(2x+y)(2x-y)+(-x+y)(5x-y)]除以-2y,其中x=-1,y=1
若2/x-1/y=3,求[y/x-y/x-y(x-y/x-x+y)]/x-2y/x的值
(x+y-5)*(x+y-5)+(x-y+3)=0 x*x-y*y
已知:3x-5y=0,求x/y,x-y/y,x-y/x
4(x+2)=1-5y 4(x+y)-3(x-y)=12
(2x+y-1)(2x-y+1)-(3x+y)(3x-y),其中x=5分之1,
(3x-y)^2+(3x+y)(3x-y),x=1,y=-2
x+y/2+x-y/6=5 2(x+y)-3(x-y)=-2
3(x+y)+2(x-y)=36 4(x+y)-5(x-y)=2
4(x-y)-3(x-y)=9 5(x-y)+2(x-y)=11
3(x+y)-4(x-y)=11,2(x-y)+5(x+y)=27
6(x-y)-2(x+y)=14 3(x-y)+(x+y)=5
二元一次方程 :2(x+y)-(x-y)=3 (x+y)-2(x-y)=1
2(x+y)-3(x-y)=1 6(x+y)+(x-y)=51
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1